Electrowetting effect on boiling point - Mohammed Farith Ikhmal Buang (Nanyang Technological University, 2022)
Over the years, there are studies that shows how electrowetting (EW) can improve the boiling performance by comparing to hydrophobic surfaces. In EW, voltage plays a huge part in the process. The contact angle of droplets will decrease as the voltage is increase. There is not much to say how the level of voltage can have an influence on boiling heat transfer parameters: boiling heat transfer coefficient (BHTC) and critical heat flux (CHF). This report will focus on the study of enhancing boiling heat transfer using EW with various level of voltage. The first part of the report will cover the fundamentals of pool boiling and heat transfer characteristics of the various boiling regimes. There will also be detailed explanation on the principle of wettability and studies on pool boiling enhancement through EW. Thereafter, the assembly and procedures of the experimental setup will be further elaborated with the help of simple diagram and actual photos. A setting where no voltage is applied to the experiment set up will also be included. The readings obtain in that setting will be used to compare with the various high level of voltage, to see the effects it has on the boiling heat transfer performance. Proper analyses were done on the collected data which includes CHF, minimum heat flux and surface temperature. Finally, it was concluded that through the experiments conducted on the various level of voltage, it was found that the higher level of voltage helps optimize the boiling heat transfer performance. Thus, this can help with further improvement on existing EW application, such as electronic chips and microprocessors.